Vıdeo Akredıtası Perguruan Tınggı Unıversıtas Internasıonal Batam - Diny Anggriani Adnas; Rachmawan Rachmawan (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Accreditation is the process of determining the eligibility of an education program, a great accreditation score will increase the public’s view of that program. Universitas Internasional Batam is one of the largest and best universities on the Batam island. In March 2019, Universitas Internasional Batam held an accreditation and gained B in the end, in order to attract public attention therefore a video about accreditation in Universitas Internasional Batam were made. The author will gain the data and information for this report using observation and documentation, then the data gained using documentation will be edited using Adobe Premiere Pro CC 2020. The Author expect that the video will attract public attention and will increase university’s image and reputation.